GEOLOGI DAN HIDROGEOLOGI DAERAH TALAWI DAN SEKITARNYA, KOTA SAWAHLUNTO, SUMATRA BARAT - Ayu Pramita, Betari
PLTU Ombilin was suspected of disposing fly-ash and bottom-ash (abbreviated as FABA) waste in the landfill location that had not been legally assessed. The concerns of environmental contamination, especially groundwater, was derived from the disposal activities. According to government decree, geological and hydrogeological aspects are one of the requisite factors in determining landfill-location’s properness, including FABA landfill area. Regional geological and hydrogeological reflecting the local’s condition were two important aspects which were needed to be assessed. Therefore, this study is aimed to identify the geologic and hydrogeological conditions (of the landfill-area and its surroundings), to study the impacts of the current FABA-disposal activities to the groundwater condition and determine the properness of the landfill area legally. Geographically, the research area was located at 692000—698000 mE dan 9928000 —9937000 mS (UTM projection) comprising an area of 54km2. The study area consisted of seven geomorphologic units: Tumpuktangah Intrusion Hills, Sarasa Intrusion Hills, Karst Hills, Complex Hills, Pyroclastic Flow Plain, Ombilin Alluvial Plain, and Lake unit. The mature-geomorphic phase was occurring in the research area accompanied by rejuvenation in several spots. The research area’s stratigraphy was divided into nine nonformal rock units which were aged from Permian to Recent. The sequence, from the oldest to youngest ones, were Limestone unit, Granodiorite unit, Porphyritic Rhyolite unit, Breccia unit, Claystone unit, Sandstone I unit, Sandstone II unit, Tuff unit, and Alluvial Deposit unit. Interpretative folds and interpretative faults were geologic structures found in the area. The first deformation caused by the transtensional regime was predicted to occur during Eocene, followed by the compressional regime at the end of Eocene. The later deformation caused by the compressional regime was predicted to occur during Miocene—Pliocene. Discovered aquifers in the research area consisted of unconfined aquifer found throughout all the rocks unit and confined aquifer in several rock units. Groundwater possessed pH values between 1,3—7,8 with value <4 plying 2% of the research area. Groundwater possessed Total Dissolved Solid (TDS) value ranged from 5—2230 mg/L with value >1000 mg/L plying 2% of the research area. TDS anomaly was found in Tandikek and was suspected to be correlated with FABA waste and landfill material. Comparison between government’s decree and the analysis concluded that PLTU Ombilin’s FABA landfill area satisfied one amidst four requirements related to the geologic and hydrogeologic condition. Data acquired were not sufficient to assess the other two requirements and left the last requirement to be unsatisfied. Further study was required to determine the unassessable points.